Non-Mycorrhizal Fungal Presence Within Roots Increases Across an Urban Gradient in Berlin, Germany - Whitehead, James; Hempel, Stefan; Rillig, Matthias C. (Frontiers in Environmental Science, 2022)
Symbioses between plants and fungi are important in both promoting plant fitness and maintaining soil structure. The ways in which these relationships change across an urban gradient is subject to debate. Here we measured root colonisation including the presence of arbuscular mycorrhizal fungi, non-mycorrhizal fungi, and root hair presence. We found no evidence of changes in levels of arbuscular mycorrhizal fungal colonisation across an urban gradient, colonisation levels being driven instead by plant community. However, we did observe an increase in non-mycorrhizal fungal colonisation in association with increasing urbanity. Additionally, we observed an urban-related increase in root hair presence. Using principal component analysis we were able to provide strong evidence for these patterns being driven by an “urban syndrome”, rather than soil chemistry. Our findings have important implications for the wider understanding of abiotic stresses on fungal endophyte presence and shed light on the impacts of urbanity upon plant roots.